Herbal drink training as a solution for dengue hemorrhagic fever treatment in Menteng Village - Dwi Hermayantiningsih; Reny Rosalina; Zahrotun Nafisah; Sudarman Rahman (Community Empowerment, 2025)
Menteng Village, located in the Jekan Raya Subdistrict, Palangka Raya City, experiences health problems due to the increasing prevalence of dengue hemorrhagic fever (DHF) during the rainy season. To equip the community with the necessary knowledge to address this issue, a community service team conducted outreach and training on making local herbal-based drink supplements to increase platelet levels in DHF patients. The outreach included information on the importance of platelets in DHF and the pharmacological properties of herbal plants such as papaya leaves, sweet potato leaves, and patikan kebo leaves. The activity continued with training on herbal infusion techniques. The evaluation results showed an increase in participants' understanding of DHF and herbal supplements, from only 27% who were at a very knowledgeable level before the activity to 80% after the activity. This activity successfully increased participants' knowledge of DHF treatment and provided practical skills in making herbal supplements.